2018
DOI: 10.1186/s12948-018-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Allergic sensitization to common pets (cats/dogs) according to different possible modalities of exposure: an Italian Multicenter Study

Abstract: BackgroundThe query “are there animals at home?” is usually administered for collecting information on anamnesis. This modality to consider exposure to pet allergens constitutes a potential bias in epidemiological studies and in clinical practice. The aim of our study was to evaluate/quantify different modalities of exposure to cat/dog in inducing allergic sensitization.MethodsThirty Italian Allergy units participated in this study. Each centre was required to collect the data of at least 20 consecutive outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…Multifaceted interventions are recommended for best results . Because Fel d 1 is such a ubiquitous allergen, sensitized individuals that successfully reduce the allergen load in their own homes will still be exposed to potentially high levels of cat allergens at work, in homes of cat‐owning family members or friends, and in public places …”
Section: Current Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Multifaceted interventions are recommended for best results . Because Fel d 1 is such a ubiquitous allergen, sensitized individuals that successfully reduce the allergen load in their own homes will still be exposed to potentially high levels of cat allergens at work, in homes of cat‐owning family members or friends, and in public places …”
Section: Current Managementmentioning
confidence: 99%
“…2 9 It is passively transferred on clothing 2,5,19 ; as a result, the allergen is ubiquitous and has been documented in homes without cats, private vehicles, and public transportation and buildings at levels (≥8 µg Fel d 1 per gram of dust) that exceed threshold value associated with sensitization. 2,5,7,[25][26][27][28][29][30][31][32][33][34] Although Fel d 1 levels in schools are detectable, they are often low and may not induce symptoms, 35 but a Swedish study found that indirect exposure to cat may be associated with worsening of asthma in cat-allergic students. 26…”
Section: Fel D1 the Ma Jor C At Allerg Enmentioning
confidence: 99%
See 1 more Smart Citation
“…These biological agents are aeroallergens, mainly lipocalins, derived by different biological fluids and/or tissue (saliva, serum, urine, dander, hair, fur) that remain in suspension for different times in relation to meteorological conditions and factors influencing their dispersion [1,2]. In recent years, the topic regarding animal allergen exposure has been treated both in pets [3][4][5] and experimental animals [6][7][8][9], and attention has been also addressed to co-exposure of allergens and endotoxins in these workplaces, although in a more restricted way [10][11][12][13][14][15]. Exposure to biocontaminants in animal facilities in USA and in the United Kingdom has received great attention [16][17][18][19] as demonstrated by the NIOSH publication in 1998 [20], where the so-called LAA (Laboratory Animal Allergy) was considered an occupational risk, and by Gordon in 2001 [21].…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of the pet(s) is the strongest predictor of elevated pet allergen levels, [10•, 36] allergen levels are also influenced by the number of pets and pet keeping habits [37, 38, 40]. However, exposure to cat and dog allergens is not limited to direct contact with pets [41, 42]. Both allergens attach easily to clothing and hair [43, 44], and are passively transported into other environments, including petless homes, schools, daycares, workplaces, hospitals and private as well as public transportation vehicles [21, 37].…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%